Comparison of the Effectiveness of Palonosetron and Dexamethasone to Prevent Postoperative Nausea and Vomiting in Patients Undergoing Uncomplicated Laparoscopic Cholecystectomy: Palonosetron and Dexamethasone to Prevent PONV: Laparoscopic Cholecystectomy - Ahmad, Samra; Ali, Sheikh Ziarat; Syed, Yashal; Chuadhary, Mehtab Tipu; Iram, Aqsa; Haq, Fizzah (Pakistan Journal of Health Sciences, 2026)
Postoperative nausea and vomiting (PONV), particularly in patients having laparoscopic cholecystectomy, continues to be a prevalent and distressing consequence after surgical operations. It leads to higher hospital stays and resource utilization, as well as patient dissatisfaction. PONV occurrences have been linked to a range of patient-specific, anesthesia- and surgery-related risk factors. Objectives: To determine the effectiveness of palonosetron compared to dexamethasone in preventing PONV in patients undergoing a laparoscopic cholecystectomy operation (uncomplicated). Methods: It was a quasi-experimental study that was conducted in the Department of Anesthesiology, Sir Ganga Ram Hospital, Lahore. The inclusion and exclusion criteria were met, and after that, 108 candidates were included and categorized into 2 groups. In patients of group A, 54 patients received 0.075mg Palonosetron (diluted in 5cc distilled water) intravenously in a single dose. In patients of group B, another 54 patients received 8mg dexamethasone intravenously. Results: Most of the patients included were female (66.7%), and the mean age of patients was 52.82 ± 8.80 years. When compared, the efficacy of both the drugs for PONV using the chi-square test (significant p-value>0.005) showed that only 20 cases (37.0%) of the group palonosetron suffered from PONV. While 42 patients (77.8%) of the dexamethasone group suffered from PONV (p-value=0.00). This showed that Palonosetron is clearly a superior drug in terms of efficacy as compared to dexamethasone. Conclusions: This study concluded that palonosetron is more effective than dexamethasone in preventing PONV in patients undergoing uncomplicated laparoscopic cholecystectomy.